THE DEVELOPMENT OF E-LKPD USING BOOK CREATOR ON FRACTION OPERATIONS MATERIAL IN ELEMENTARY SCHOOL: PENGEMBANGAN E-LKPD MENGGUNAKAN BOOK CREATOR PADA MATERI OPERASI HITUNG PECAHAN DI SEKOLAH DASAR - Tri Yudha Setiawan; Aidil Fikri (MaPan : Jurnal Matematika dan Pembelajaran, 2022)
Through the online learning system that has been implemented, many problems arise. The online teaching and learning process causes students to feel bored while learning and does not fully convey the material to students. The purpose of this study was to determine the process of developing E-LKPD which was made by the author of the book. This research is a research and development (R&D) research using the DDD-E model (Decide, Design, Develop, and Evaluate). Sources of data in this study were three teachers and students. The instrument used in this study was a questionnaire distributed to teachers and students. E-LKPD was developed by fulfilling the valid, practical, and effective criteria. E-LKPD is declared valid with an average result of 88% with very feasible criteria. E-LKPD is declared practical with an average result of 88% with very good criteria. E-LKPD is declared effective with an average result of 94% with very good criteria. It is concluded that the E-LKPD is very suitable for use for elementary school students and is able to increase understanding and motivation to learn fractional arithmetic operations.